1383. Necrotizing Fasciitis and Streptococcus pyogenes (GAS) Infection Seasonality and Risk Factors for Infection— a Multicenter Research Network Study. (15th December 2022) - Kennis, Matthew; Tagawa, Alex; Kung, Vanessa; Montalbano, Gabrielle E; Narvaez, Isabella; Franco-Paredes, Carlos; Barahona, Lilian Vargas; Shapiro, Leland; Chastain, Daniel B; Henao-Martínez, Andrés F
Abstract: Background: Streptococcus pyogenes causes acute pharyngitis and type II necrotizing fasciitis. Seasonal variations in the incidence of S. pyogenes infections are not robustly characterized. We aim to identify seasonal variations and risk factors of S. pyogenes infections and all causes of necrotizing fasciitis. Methods: From 2010 to 2019, we identified all infectious adult cases of S. pyogenes using ICD-10 diagnoses and lab results (PCR and antigen-based assays) and cases of necrotizing fasciitis using ICD-10 diagnoses within a federated research network. We extracted seasonal (quarterly) incidence rates. We used an autoregressive integrated moving average (ARIMA) model to assess the seasonality of the cases (6-month intervals). Demographic characteristics and 3-month outcomes of S. pyogenes pharyngitis were compared to a cohort of patients with acute upper respiratory illnesses excluding S. pyogenes. Results: We identified 238, 088 cases of S. pyogenes pharyngitis and 26, 931 cases of necrotizing fasciitis in adults. S. pyogenes infection average incidence was higher during the winter than the summer: 0.34 vs. 0.20 cases per 1, 000 patients. Necrotizing fasciitis diagnoses were highest during the summer months (average 0.026 per 1000 patients). There was a significant ARIMA seasonal variation in the time series analysis for S. pyogenes infections (p=0.006) (figure 1). However, necrotizing fasciitis was not significant (p=0. 0.79) (Figure 2). Compared to adults with acute respiratory infections other than S. pyogenes, adults with S. pyogenes pharyngitis were more likely to be younger (25.8 ± 14.9 vs. 45.4 ± 19.9 years old, p< 0.0001) and of Hispanic or Latino ethnicity (11% vs. 8%, p < 0.0001). For age-matched outcomes, adults with S. pyogenes pharyngitis had lower rates of hospitalization (0.888% vs. 1.714%, p< 0.0001) and mortality (0.114% vs. 0.174%, p< 0.0001) at three months relative to adults with acute respiratory infections other than S. pyogenes . Figure 1. Seasonal variation of adults with established ICD code or testing for Streptococcus pyogenes (GAS) infections Figure 2. Seasonal variation of adults with established ICD code for necrotizing fasciitis Conclusion: Peaks in S. pyogenes infections are more likely to occur in the winter months, although spring and fall seasons can display variably high rates of S. pyogenes year over year. Necrotizing fasciitis of any microbiological did not show a significant seasonal variation. Disclosures: All Authors : No reported disclosures.